Photometric observations of two very long period eclipsing binaries: AZ Cas and EE Cep - Mikolajewski, M.; Zola, S.; Kurpinska-Winiarska, M.; Galan, C.; Gazeas, K.; Niarchos, P.; Stachowski, G.; Winiarski, M.; Siwak, M.; Drozdz, M.; Ogloza, W.; Majewska, A.; et al. (Spectroscopically and Spatially Resolving the Components of the Close Binary Stars, 2004)
This paper reports new photometric observations of minima of two very long-period eclipsing systems: AZ Cas (P=3402 °}) and EE Cep (P=2050 °). In order to match the observed depth of the primary minimum of AZ Cas we had to introduce a third light component. For EE Cep, the shape of the eclipse can be explained by a model that includes a dark precessing disk in the system.